A identificação e a investigação criminal genética à luz dos direitos fundamentais e da lei 12.654/12 - Sauthier, Rafael (2014)
This dissertation is the conclusion task of the Criminal Sciences Master Degree Course, Penal System and Violence concentration area, and Contemporary Juridical and Penal Systems research guideline. It studies the criminal genetic identification and investigation procedures in its best performance, and in compliance with the fundamental rights. In the center of this debate there is the Law number 12.654/12. In order to be able to perform such analysis, this research begins with a bibliographic study, including comparative law, and deepens into concepts concerning to DNA, biology, the genetic typing procedures, the DNA data bank for criminal purposes and its implantation, and the related fundamental rights and their applicability. Therefore this study notices that despite the dactyloscopy is the cheapest, quickest and safest method, in some situations, especially when the identity determination merges into the search of the criminal authorship (investigative task), the genetic typing offers the best solutions because of the perennial characteristic of the biological samples. This process allied to a computerized support of data increases substantially the performance of the genetic law enforcement. However, some fundamental rights are affected in various moments in the use of the mix typing-bank for the criminal identification and investigation. Hence, the research arrives to the final phase: evaluating when these restrictions to the fundamental rights configure violations and when they arise from the application of the proportionality in the collisions of fundamental rights. In addition, it also searches a solution that does not affect the effectiveness of such instruments of criminal identification and investigation with respect to the dignity of the human being. If such restrictions arise from simple violations of what is ruled in the Federal Constitution, there is no solution to validate such affection. However, when we are dealing with collisions of fundamental rights, the possible solution is the application of the proportionality principle. In the end, this research concludes that considering the legal format ruled in the Law number 12.654/12, it is possible to reach the desired results in the use of the mix typing-bank for criminal identification and investigation in compliance with the dignity of the human person and related the fundamental rights